Florakirk Bermudagrass - Paul Mislevy; William F. Brown; L. S. Dunavin; W. S. Judd; Robert S. Kalmbacher; Thomas A. Kucharek; Joseph W. Noling; O. C. Ruelke; R. M. Sonoda; R. L. Stanely, Jr. (EDIS)
This document is SS-AGR-183, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published (as Circular S395) August 1995. Revised October 2002.